British Invention Show (BIS) 2012 @ Barbican Exhibition Centre, London, United Kingdom - Noor Syahidah, Sabran (Penerbit UMP, 2012)
Universiti Malaysia Pahang (UMP) has gone it again at the international level after collecting two gold medals, a silver medal and a Special Award (Platinum) in the exhibition and competition on research project at the British Invention Show (BIS) 2012.